Strategy for Women Scavengers in Fulfilling the Family Economy in Makassar City (The Case of Scavengers Involving Toddlers in Urban Areas) - Mardiana Ethrawaty Fachry; Nur Ikhsan; Mansyur Radjab; Herawaty; Fatmawati; Sitti Bulkis (International Journal of Applied Biology, 2022)
Poverty is still a problem in urban areas. Limited skills and employment have caused women from low-income families to also seek work as scavengers or collectors of waste and used goods to help support their family's economy. This study aims to find the characteristics of female scavengers in responding to poor women fulfilling their family's economy. The involvement of children under five in the scavenging process is also a review in finding the distribution of gender roles in scavenger households. This research was conducted in Makassar City using a qualitative approach. Data were obtained from 25 families of female scavengers. The study found that women in scavenging activities involved children between the ages of 1 and 5 years, which was a domestic role and a strategy to get additional income from the community's compassion. Scavenger women make an economic contribution to the family between 40% and 77%. The involvement of children under five in the scavenging process is a form of child exploitation which has yet to become the attention of the Makassar city government.